Mewujudkan Indonesia sebagai Negara Poros Maritim Dunia - Arman Tjoneng (Faculty of Law, Maranatha Christian University, 2015)
Indonesia, a country that has given abundant natural resources with strategic geographical position and supported by the geostrategic, geopolitical, geoekonomi and geososial culture as the largest archipelago in the world. Indonesia maritime glories of the past to make the government plans to make Indonesia as the Axis Maritime World. This has become a priority of the government Jokowi-JK.With all the challenges, related to the implementation of the vision of Indonesia as Axis Maritime world, so many things need to be corrected and must be repaired as well as various strategic steps to be taken by the government in particular is associated mindset (mind-set) of Indonesia, reform the legal system and the enforcement of maritime sovereignty in Indonesia.In order to realize the vision of Indonesia as a maritime axis, the active participation of all parties, especially the government and the all community are needed to restore the glory of Indonesia in the field of maritime with the slogan